A Robust Multiobjective Mathematical Model Optimizing Stock Portfolio - Mehran Sadri; Alireza Sadeghi; Mahdi Madanchi Zaj; Esmaeel Afzoon; Helia Dardaei-beiragh (Discrete Dynamics in Nature and Society)
The present paper investigates the problem of capital portfolio selection under uncertain conditions and uses a robust optimization approach for modeling. The model provided in this paper is a three-objective model that aims to maximize returns, maximize liquidity, and minimize risk. The data extracted from the site of the Tehran Stock Exchange are as follows. These data are related to twenty shares from July 2020 to July 2021. The robust approach used in this research has been analyzed by the real data of the Tehran Stock Exchange and then the optimal portfolio for different robust costs has been formed by solving the robust model. In the following section, the relevant model is solved through real stock market data and using the goal programming approach, and the results are investigated and analyzed.